Synthesis of a New Aza-crown Ether Containing Pendant Carboxylate Groups, Its Th4+ and UO22+ Complexes and Thermodynamic Properties in Aqueous Solution - Bi, Jian-Hong; Xie, Fu-Xin; Zhao, Xiang-Da; Chen, Li-Qin; Xu, Ji-De; Ni, Shi-Sheng (Asian Journal of Chemistry, 2012)
A novel tetraazamacrocycle containing pendant carboxylate group L1H4 (5,12-diphenyl-7,14-dimethyl-1,4,8,11-tetraazamacrocyclotetradecane-N,N’,N”,N”’-tetraacetic acid) and its complexes with Th4+ and UO22+ have been synthesized and characterized by elemental analyses, IR, 1H NMR spectra, conductivity measurement, TG-DTA analyses and X-ray powder diffraction. The stability constants of mononuclear complexes of L1H4 with the Th4+ and UO22+ were determined at 35 ± 0.1 , 45 ± 0.1 and 55 ± 0.1 ºC in 0.5 mol.L-1 KNO3 solution by means of potentiometric and computer fitting. The aH and aS of the coordination reactions in the aqueous solution were given.